Comparison of Complication of Postpartum Intrauterine Contraceptive Device With Interval Placed IUCD: PPIUCD VS Interval Placed IUCD - Khalid, Hina; Syed, Sadaf Zahra; Waheed, Fatima; Iqbal, Fouzia; Mehmud, Quraa; Khalid, Aysha (Pakistan Journal of Health Sciences, 2023)
For prevention of unintended and closed interval pregnancies through the first year following childbirth, postpartum family the planning is required. A wide range of reliable and cost-effective contraceptive methods are available for postpartum women. Objective: To compare the frequency of complications of postpartum intrauterine contraceptive device (PPIUCD) versus interval placed intrauterine contraceptive device (IUCD). Methods: It was a randomized control clinical trial which was conducted in Unit 3, Department of Obstetrics & Gynecology, Lady Willingdon Hospital, Lahore. The time period of this study was 6 months extending from January 2018 to June 2018. After fulfilling the inclusion criteria, 160 patients were enrolled in the study. These patients were followed up for time period of 6 months in both groups. The complications named perforation, pelvic infection and expulsion were noted. All the gathered information regarding variables was analyzed on SPSS version 20.0. Results: The mean age and gestational age of females of the PPIUCD group was 26.50±5.05 years and 38.94±1.42 weeks and interval IUCD group was 28.25±4.40 years and 39.08±1.29 weeks respectively. In this study the pelvic infection was noted in 8 females in which 2 were from PPIUCD group and 6 were from interval IUCD group. Statistically insignificant difference was found between the study groups with pelvic infection i.e. p-value=0.147. Expulsion was noted in 1 female from PPIUCD group and 3 females from interval IUCD group. The difference was insignificant (p>0.05). Conclusions: There was no statistical difference found in frequency of complications with PPIUCD versus interval placed IUCD.